Analisis Komparatif Kinerja Reksa Dana Syariah dan Reksa Dana Konvensional di Masa Pandemi - Izzuna Davi; Slamet Haryono (Jurnal Ilmiah Ekonomi Islam, 2022)
This study aims to compare and see the performance of Islamic mutual funds and conventional mutual funds during the pandemic. This study uses a type of research with a quantitative approach. The samples used in this study were conventional mutual funds and Islamic mutual funds. The source of data in this study is secondary data from the Net Asset Value per unit (NAV/unit) of sharia mutual funds and conventional mutual funds available on the OJK website. The analytical method used is the comparative method and the average difference test using the independent sample t-test method, with the SPSS program and the Sharpe method to determine the best performance of stock mutual fund ratings. The results show that the performance of conventional stock mutual funds with an average Sharpe index of 0.026 is superior to the performance of Islamic mutual funds with an average Sharpe index of 0.021, while based on the independent sample t-test test, it is proven that there is no significant difference between the performance of Islamic stock mutual funds and performance of conventional equity mutual funds, with a 2-tailed sig value of 0.498 > 0.05.